2022
DOI: 10.1111/imm.13567
|View full text |Cite
|
Sign up to set email alerts
|

IKKα aggravates renal fibrogenesis by positively regulating the Wnt/β‐catenin pathway

Abstract: AKI (acute kidney injury) with maladaptive repair plays exacerbated role in renal fibrosis characterized by tubulointerstitial fibrosis. Previously, we reported that IKKα contributed to kidney regeneration and inhibited inflammation. Here, we first identified the role and mechanism of IKKα on TGF-β1-induced fibrosis in human tubular epithelial cells and fibrotic kidneys. IKKα was up-regulated in kidney tubular epithelium in unilateral ureteral obstruction (UUO) and unilateral ischemic reperfusion injury (UIRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Regardless of the origin, increasing evidence strongly supports that the resultant myofibroblasts share the same properties and signalling cascade events that lead to their formation. The activity of Wnt/β-catenin signalling is implicated in the fibrogenesis of multiple organs [ 45 , 46 ]. The increased nuclear accumulation of β-catenin was observed in human tissue samples from systemic scleroderma [ 47 ], idiopathic pulmonary fibrosis [ 48 ], and liver cirrhosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the origin, increasing evidence strongly supports that the resultant myofibroblasts share the same properties and signalling cascade events that lead to their formation. The activity of Wnt/β-catenin signalling is implicated in the fibrogenesis of multiple organs [ 45 , 46 ]. The increased nuclear accumulation of β-catenin was observed in human tissue samples from systemic scleroderma [ 47 ], idiopathic pulmonary fibrosis [ 48 ], and liver cirrhosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have reported that EMT of TECs plays a crucial role kidney fibrogenesis (Hu, Tang, Liu, Hu, & Pan, 2022; Kandel & Singh, 2022; Wang et al, 2022; Zhang, Xing, & Zhao, 2021). Initiation of fibrosis occurs when the toxins/stimuli cause TECs and kidney tissue to damage or dysfunction (Jorgacevic et al, 2022; Zhang et al, 2023). As expected, mechanisms responsible for such toxins/stimuli‐induced detrimental injury are mainly inflammation and repairing process (Ovadya & Krizhanovsky, 2015; Yang et al, 2021).…”
Section: Emt and Kidney Fibrosismentioning
confidence: 99%